2011
DOI: 10.1186/1471-2296-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Urine culture doubtful in determining etiology of diffuse symptoms among elderly individuals: a cross-sectional study of 32 nursing homes

Abstract: BackgroundThe high prevalence of bacteriuria in elderly individuals makes it difficult to know if a new symptom is related to bacteria in the urine. There are different views concerning this relationship and bacteriuria often leads to antibiotic treatments. The aim of this study was to investigate the relationship between bacteria in the urine and new or increased restlessness, fatigue, confusion, aggressiveness, not being herself/himself, dysuria, urgency and fever in individuals at nursing homes for elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 28 publications
1
47
1
1
Order By: Relevance
“…One study found enterobacteriaceae species to account for 34.8% of remaining cultures, while the second distributed these between Klebsiella (12%) and Enterococcus faecalis (8%). 21,22 Other common hospitalassociated pathogens like Pseudomonas aeruginosa, vancomycin-resistant enterococci, and Candida spp have been identified in this population as well. 23 Patients with indwelling catheters are uniquely at higher risk for biofilm-associated organisms, polymicrobial infections, and yeast colonization and infection.…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%
“…One study found enterobacteriaceae species to account for 34.8% of remaining cultures, while the second distributed these between Klebsiella (12%) and Enterococcus faecalis (8%). 21,22 Other common hospitalassociated pathogens like Pseudomonas aeruginosa, vancomycin-resistant enterococci, and Candida spp have been identified in this population as well. 23 Patients with indwelling catheters are uniquely at higher risk for biofilm-associated organisms, polymicrobial infections, and yeast colonization and infection.…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%
“…was the second most common (12%) followed by Enterococcus faecalis (8%). 20 It is postulated that the postmenopausal state, worsening incontinence and disability, and greater exposure to antibiotics changes the vaginal microbiome of older women, thereby changing the profile of uropathogens causing UTI in community-dwelling and institutionalized women. Fig.…”
Section: Microbiologymentioning
confidence: 99%
“…Thus, in most cases urinary culture should not be obtained in cases of a negative dipstick for leukocyte esterase and nitrite, and causes other than UTI should be evaluated. Urine culture alone often is not helpful in evaluating diffuse nonspecific symptoms in older long-term care residents 20 and should not be performed routinely in asymptomatic patients. 1 Fig.…”
Section: Diagnosis Of Uti In Long-term Care Facilitiesmentioning
confidence: 99%
“…The most common sign reported for UTIs is altered mental status which includes symptoms such as Bconfused, more irritable, crying, aggressive, agitated, and less compliant^ [26]. Also, Sundvall et al found no correlations between UTI symptoms and bacteriuria among 651 nursing home residents [27]. The lack of specificity of these symptoms can create challenges with diagnosing UTIs.…”
Section: Non-specific Presentation Of Signs and Symptomsmentioning
confidence: 97%